A review on interfacial structure optimization and its mechanism on the properties of carbon reinforced metal-matrix composites. Issue 5 (4th May 2023) - Cao, Jiaming; Li, Fengjia; Yang, Qingchao; Zhan, Ke; Yang, Zheng; Wang, Zhuo; Zhao, Bin
ABSTRACT: Metal-matrix composites (MMCs), especially the novel carbon materials such as graphene (Gr), carbon nanotubes (CNTs) and diamond, reinforced MMCs, have received increasing attention from academia and industry due to their potential excellent properties. In carbon reinforced MMCs, the interface, as the 'bridge' between the matrix and the reinforcement, has great influence on the transfer of stress, thermal and electrical conductivity, and plays an important role to determine the properties of the composites. The structure and properties of interface between the carbon and metal matrix can be designed and enhanced. This paper summarizes the important research progress on the interfacial structure optimization method for carbon reinforced MMCs, and discussed the mechanism of the carbon/metal interface on the properties of the composites. Finally, the problems and development of the interface of carbon reinforced MMCs are prospected. GRAPHICAL ABSTRACT: uf0001